Characterization and visualization of the liposecretion process taking place during ceiling culture of human mature adipocytes. Issue 7 (18th December 2018) - Côté, Julie Anne; Gauthier, Marie‐Frédérique; Ostinelli, Giada; Brochu, Dannick; Bellmann, Kerstin; Marette, André; Julien, François; Lebel, Stéfane; Tchernof, André
Abstract: Objective: To investigate and further characterize the process of mature adipocyte dedifferentiation. Our hypothesis was that dedifferentiation does not involve mitosis but rather a phenomenon of liposecretion. Methods: Mature adipocytes were isolated by collagenase digestion of human adipose tissue samples. Ceiling cultures were established using our six‐well plate model. Cells were treated with cytosine β‐d ‐arabinofuranoside (AraC) or vincristine (VCR), two agents blocking cell division, and were compared with vehicle. Liposecretion events were visualized by time‐lapse microscopy, with and without AraC in adipocytes transducted with a baculovirus. Microscopic analyses were performed after labeling phosphorylated histone 3 and cyclin B1 in ceiling cultures. Results: Treatment with AraC almost entirely prevented the formation of fibroblasts up to 12 days of ceiling culture. Similar results were obtained with VCR. The antimitotic effectiveness of the treatment was confirmed in fibroblast cultures from the adipose tissue stromal‐vascular fraction by proliferation assays and colony‐forming unit experiments. Using time‐lapse microscopy, we visualized liposecretion events in which a large lipid droplet was rapidly secreted from isolated mature adipocytes. The same phenomenon was observed with AraC. This was observed in conjunction with histone 3 phosphorylation and cyclin B1 segregation to the nucleus. Conclusion: Our results support the notion that dedifferentiation involves rapid secretion of the lipid droplet by the adipocytes with concomitant generation of fibroblast‐like cells that subsequently proliferate to generate the dedifferentiated adipocyte population during ceiling culture. The presence of mitotic markers suggests that this process involves cell cycle progression, although cell division does not occur. Abstract : The dedifferentiation process involves rapid secretion of the lipid droplet by adipocytes, with concomitant generation of fibroblast‐like cells that subsequently proliferate to generate the dedifferentiated adipocyte population during ceiling culture. The presence of mitotic markers suggests that this process involves cell cycle progression, although cell division does not occur.